Penerapan Pasal 27 Ayat (3) UU ITE dalam Perkara Pencemaran Nama Baik melalui Media Sosial terhadap Kelompok Orang - Rezkyta Pasca Abrini Daeng Ngiji; Sigid Suseno; Budi Arta Atmaja (Universitas Bumigora, 2022)
Defamation is first regulated in Article 310 of the Criminal Code to protect the honor and reputation of each individuals. Defamation on electronic media is regulated in Article 27 Paragraph (3) of the ITE Law. Based on the Constitutional Court Decision Number 50/PUU-VI/2008, the implementation of Article 27 Paragraph (3) of the ITE Law refers to the Article 310 of the Criminal Code which requires a complaint (klacht). The implementation of Article 27 Paragraph (3) of the ITE Law in the cases of defamation of a group of people often creates confusion due to the unclear person being addressed. The implementation of this Article as an absolute complaint offense in defamation cases addressed to a group of people is still improper because the complaint in this case initiated by someone who is not directly harmed but as a group. This Article is still being implemented based on the interpretation of each law enforcement officials which causes its implementation does not reflect the legal certainty. The research method used is normative juridical approach with analytical descriptive specifications, that describes the regulations with legal theory and practical implementation.